Cervical cancer: From diagnosis to treatment - Camarço , Maria Gabryella Pereira da Silva; Jales, Davi Nogueira; Leitão , Cadidja Suzzi Oliveira; Filho , Alcides Mendes da Luz; Kittlaus , Isabella; Silva , Emília Moura; dos Santos , Maria Eduarda Campêlo; Júnior , Vilmar Barbosa de Sousa; de Almeida , Maria Clara Barbosa; Coêlho , Francisberg Dias; Júnior , Antonio de Pádua Andrade; Frota , Sarah Nicolly Romualdo; et al. (Seven Editora, 2024)
Introduction: Cervical cancer is primarily caused by Human Papillomavirus (HPV) infection and remains a global public health concern. Methodology: This article performs an integrative review of the literature, covering national and international scientific articles. Databases such as VHL, SciELO, LILACS and PubMed were consulted to compile the information. Discussion: Early diagnosis is essential and can be carried out through the Pap smear test and, more recently, by the detection of HPV. Treatment varies depending on the stage of the disease and may include surgery, radiation therapy, chemotherapy, or a combination of these modalities. Conclusion: Advances in research have improved the understanding of the mechanisms of cervical cancer development, influencing public health policies to promote effective prevention strategies, such as mass vaccination programs and educational campaigns. DOI:https://doi.org/10.56238/sevened2024.016-024